Dynamic fluid interface formation in microfluidics: Effect of emulsifier structure and oil viscosity. (February 2018) - Muijlwijk, Kelly; Li, Xuezhu; Berton-Carabin, Claire; Schroën, Karin
Abstract: Microfluidic devices are known for their accurate control of emulsification, but are less known for their suitability to investigate involved dynamic mechanisms. We previously showed that a microfluidic Y-junction can be used to measure interfacial tension in the millisecond time-scale, at high interface expansion rates, and under convective mass transport. In the present work, we further use this device to elucidate and compare dynamic adsorption behaviour of water- or oil-soluble surfactants, in combination with different alkanes. We found that oil viscosity affects adsorption of the oil-soluble surfactant Span 20 because surfactant transport is influenced by viscosity through the internal velocity. Conversely, adsorption of the water-soluble surfactant Tween 20 was not affected by oil viscosity. When comparing surfactant adsorption rates, it was clear that surfactant structure became more important when more surfactants were present at the interface; Tween 20 adsorption was slower than Span 20 because of steric repulsion at the interface. Graphical abstract: Highlights: The Y-junction method can be used for a variety of oils and emulsifiers. Internal oil velocity increases with decreasing oil viscosity. Interfacial tension of Span 20 and Tween 20 was quantified and compared. A window of operation was compiled that allows characterisation of adsorptive behaviour.